Chromosome-scale genome assembly of Korean goosegrass (Eleusine indica) - Solji Lee; Changsoo Kim (Scientific Data)
Abstract Goosegrass, belonging to the genus Eleusine within the Chloridoideae subfamily, is often one of the problematic weeds with strong invasiveness, competing with crops for essential survival resources. Although a chromosome-level genome assembly of E. indica from China was published last year, the present research focuses on a population of E. indica native to South Korea. Considering the high genetic variability among wild E. indica populations, constructing multi-reference genomes from geographically distinct populations is crucial for comprehensive weed management strategies. In this study, we sequenced and assembled the whole genome using PacBio long read and Illumina short read sequencing platforms. We then combined Pore-C sequencing technology to successfully anchor 255 contigs to nine pseudochromosomes. The chromosome-level genome assembly showed a high level of completeness with a 97% score according to BUSCO analysis results. Repetitive sequences accounted for 97% of the genome assembly, and 26,836 protein-coding genes were predicted. The high-quality genome assembly of E. indica will serve as a valuable genetic resource to enhance our understanding of weed control research.